Constitutional Analysis of Religious Moderation Policy in Serbia: Between Legal Precepts and Social Norms - Nuroniyah, Wardah; Krajišnik, Vesna; Prastiwi, Navira Shandra (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This study examines the alignment between Serbia’s religious moderation policies and its constitutional guarantees of religious freedom, secularism, and non-discrimination. While Serbia’s 2006 Constitution enshrines these principles, the practical application of religious policies reveals discrepancies shaped by social norms and dominant religious narratives. The preferential treatment of